Pengaruh Persepsi Etika Bisnis Islam Terhadap Perilaku Pedagang Batak Muslim di Jakarta Studi Kasus Pada Organisasi Pedagang Batak Muslim KKMM (Kerukunan Keluarga Masyarakat Mompang Jae) - Ustman Hady HP; Dina Fitrisia Septiarini (Universitas Airlangga, 2014)
This research was aimed to find out the effect of Islamic business ethic’s perception against the behavior of Batak Moslem’s merchants in Jakarta. This research used questionmaires in primary data collection and quantitative approaches. Experiments were done using simple linear regression, where the dependent variable (Y) is behavior of Batak Moslem’s merchant and the independent variable (X) is Islamic business ethics. The research sample was taken by probability sampling with simple random sampling method. Theresearch sample was 65 Batak Moslem’s merchants who were members of KKMM in Jakarta.Based on the findings, it obtained simple linear regression equation: Y = 22,376 + 0,279X. The results of this research showed that the influence of Islamic business ethics has positive effect and signifficant against the behavior of Batak Moslem’s merchants who were members of KKMM in Jakarta.The R2 on this research showed the number 0.423, which mean that 42.3% of behavior of Batak Moslem’ merchants can be explained by the variables of Islamic business ethics. These results also explain that there are other variables were greater (57.7%) were able to explain the behavior of Batak Moslem’s merchants.